PARAMETER OPTIMIZATION OF SPIRAL DRILL PIPE FOR ANCHOR RECYCLING EQUIPMENT BASED ON PARTICLE SWARM OPTIMIZATION ALGORITHM - LI Ming; SUN JuTao; TIAN LiYong; YU Ning; LI RuYu; JIA XiaoMing (Jixie qiangdu)
In order to improve the drilling efficiency and reduce the weight of the anchor recycling equipment,it took spiral drill pipe of the anchor recycling equipment as the research object,by selecting the inner and outer diameter of the drill pipe,blade thickness,pitch,helix angle,speed,blade number and blade height as the optimizing parameters. It chosen the highest efficiency in transport,the lightest in weight and the highest rate in secondary crushing as the ideal goal of the drill pipe optimization,the result indicates that the drilling efficiency is increased by 31. 4%,the weight is reduced by 12. 7% and the secondary crushing rate is increased by 48. 7% based on particle swarm optimization. The efficiency of the recovering has been improved,and the wear-resisting degree and intensity of the spiral pipe have been enhanced.